If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 * 2 = -2(-5) + -4 Multiply 3 * 2 6 = -2(-5) + -4 Multiply -2 * -5 6 = 10 + -4 Combine like terms: 10 + -4 = 6 6 = 6 Add '-6' to each side of the equation. 6 + -6 = 6 + -6 Combine like terms: 6 + -6 = 0 0 = 6 + -6 Combine like terms: 6 + -6 = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 5*2=3(-5)+20 | | 3x-12-5x-10= | | 36+6X=34-4X | | -4=6x+7x+9 | | 8*(2p-4)*3p=20 | | 6x+1+5x=-65 | | a+10=b+2 | | 1+2x=x-2-4x | | -2x-5y=-27 | | 14(d+30)=-196 | | -4+4x-5x=-14 | | 3f=(2f+8) | | 6X-12+4X-1=-X+12-3X+5 | | x+(x+10)+2x=98 | | 4x+3=x+x+29 | | 2t-1=2t-5 | | 4y+3=y+21 | | 4y+3=y+22 | | 625-25x=0 | | (35x+67y)+(-20x+41y)= | | f(x-1)=x^2+3 | | f(x-1)=x^2-3 | | 14d+30=196 | | 14z=3(4z+3) | | 10x^3-11x^2-6x=0 | | 2x-1+3=4 | | 32=-0.8m | | -3.2x=14.4 | | -1.25+.25x=0 | | -1.25+25x=0 | | x+(-26)=52 | | 3x^4+12x^2=12x^3 |